Treatment with palbociclib and tislelizumab for CDKN2A-mutated and PD-L1-positive advanced intrahepatic cholangiocarcinoma: a case report and literature review - Liang, Yajun; Hu, Liya; Wu, Huanlei; Yin, Tiejun; Zhang, Jun (Frontiers in Oncology, 2024)
Background: Intrahepatic Cholangiocarcinoma(ICC) is the second most common primary liver malignancy with a steadily increasing incidence worldwide. ICC has insidious onset, rapid progression and poor prognosis. More multidisciplinary clinical studies are needed to continuously explore safer and more efficient diagnosis and treatment modes for ICC.A 66-year-old female with ICC rapidly developed systemic multiple metastases after surgery and the first-line two-drug combination chemotherapy was not effective.Due to cyclin dependent kinase inhibitor 2A (CDKN2A) mutation and programmed cell death-ligand 1 (PD-L1) positive, a partial response (PR) and progression-free survival (PFS) of 9.5 months were achieved after second-line treatment with cyclin-dependent kinase 4/6 inhibitor (CDK4/6i) combined with immunotherapy. The patient developed thromboembolism 7 months after treatment and died with disseminated intravascular coagulation (DIC).The combination of targeted and immune therapy has revealed a potentially effective regimen for the effective treatment of patients with ICC, which needs to be observed in larger clinical studies. Thromboembolism rates in real-world patients treated with CDK4/6 inhibitors are higher than those reported in clinical trials, and the application of prophylactic anticoagulation in this patient population may be questionable.